Relationship of thyroid function with body fat, waist circumference, sub-cutaneous and visceral adipose tissue in eu-thyroid female subjects - Mukherjee, Sanhita; Deoghuria, Debasis; Mukhopadhyay, Diptakanti (International Journal of Research in Medical Sciences, 2019)
Background: The relationship between thyroid function, body weight and central obesity in euthyroid individuals has been given a great medical concern. Central abdominal adiposity can be divided into adipose tissue present in subcutaneous areas (SCAT) and visceral areas (VAT). The type of adiposity may be implicated in the associations of thyroid function parameters with obesity. The aim of the present study was to evaluate thyroid function and its possible relationship with BMI, body fat percent, waist circumference, SCAT and VAT in eu-thyroid female subjects. Methods: Randomly selected eu-thyroid female subjects were included in this study. Their BMI was estimated by metric method, body fat percent was measured by Harpenden skin fold caliper. Ultrasound (US) was used to assess regional adiposity. Serum TSH was measured from fasting serum sample by Enzyme-linked-immuno-sorbant (ELISA) Assay. Data was analysed by SPSS (version 18). Results: A positive linear association was found between serum TSH level and BMI, body fat percent, waist circumference and VAT. (r=0.342, p <0.002, r=0.628, p <0.00, r=0.289, p <0.009, r=0.375, p <0.000). No significant association was found with SCAT and TSH. There is gradual increase in serum TSH values among three BMI groups i.e. normal weight (BMI <23 kg/m2), over-weight (BMI 23.00-24.99 kg/m2), and obese (BMI >25 kg/m2) females. Body fat percentage, BMI and VAT were found to be significant independent predictors of TSH. Conclusions: Selective reduction of visceral fat may induce greater beneficial effects on the parameters of thyroid hormones than subcutaneous fat reduction.